Combustion synthesis and structural characterization of the TiB2–(Na2O·2B2O3–Al2O3) composites. Issue 2 (March 2015) - Buixaderas, Elena; Anghel, Elena Maria; Atkinson, Irina; Simon, Patrick; Bratan, Veronica; Petrescu, Simona
Abstract: Two TiB2 :(Na2 B4 O7 –Al2 O3 )=3:5 and TiB2 :(1.28Na2 B4 O7 –Al2 O3 )=6:7 compositions, named 5DB and 7DB respectively, were prepared by combustion synthesis in simultaneous mode at 800, 900 and 1000 °C. X-ray diffraction, differential scanning calorimetry (DSC), UV–vis and room and high temperature Raman measurements were carried out to investigate the combustion products. The crystalline phase of the 5DB composite yielded at 1000 °C (5DB_1000), which represents 62 wt%, mostly consists of TiB2 (93 wt%) while Ti2 O3 accounts for only 7 wt%. Also, the Na2 Al2 B2 O7 compound was found to crystallize in the borate glassy matrix of the (5/7) DB composites obtained at the lower combustion temperatures. Proportion of the tetrahedral boron atoms, N4, in the blank and embedding sodium aluminium borate matrices was found from the high frequency Raman spectra using a constrained-width model in order to agree with the literature NMR data. The oxidation stability below 600 °C of the TiB2 crystallites in the (5/7) DB composites was proved by in-situ Raman measurements in air.